2015
DOI: 10.1186/s12943-015-0287-3
|View full text |Cite
|
Sign up to set email alerts
|

Receptor protein tyrosine phosphatase beta/zeta is a functional binding partner for vascular endothelial growth factor

Abstract: BackgroundReceptor protein tyrosine phosphatase beta/zeta (RPTPβ/ζ) is a chondroitin sulphate (CS) transmembrane protein tyrosine phosphatase and is a receptor for pleiotrophin (PTN). RPTPβ/ζ interacts with ανβ3 on the cell surface and upon binding of PTN leads to c-Src dephosphorylation at Tyr530, β3 Tyr773 phosphorylation, cell surface nucleolin (NCL) localization and stimulation of cell migration. c-Src-mediated β3 Tyr773 phosphorylation is also observed after vascular endothelial growth factor 165 (VEGF165… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 42 publications
4
45
0
7
Order By: Relevance
“…Interestingly, VEGF was shown to induce the translocation of nucleolin from the nucleus to the cell membrane, through the activation of a signaling pathway involving receptor protein tyrosine phosphatase b/z (RPTPb/z), which culminates in nucleolin phosphorylation by PI3K 296 . Phosphorylation regulates nucleolin's subcellular localization, and has been correlated with metastatic potential in various carcinomas 254 .…”
Section: Role Of Nucleolin In Tumorigenesis and Metastizationmentioning
confidence: 99%
“…Interestingly, VEGF was shown to induce the translocation of nucleolin from the nucleus to the cell membrane, through the activation of a signaling pathway involving receptor protein tyrosine phosphatase b/z (RPTPb/z), which culminates in nucleolin phosphorylation by PI3K 296 . Phosphorylation regulates nucleolin's subcellular localization, and has been correlated with metastatic potential in various carcinomas 254 .…”
Section: Role Of Nucleolin In Tumorigenesis and Metastizationmentioning
confidence: 99%
“…The decrease of VEGF expression was further verified by western blot analysis of tissue protein extracts. At the same time, the expression of PTN, which has been shown to limit VEGF functions, 9,10 was significantly increased in the Stent group as compared with the Control group (Figure 7).…”
Section: Immunohistochemistry and Western Blot Analysesmentioning
confidence: 77%
“…On the other hand, Ptn directly binds to VEGF and inhibits VEGF-induced endothelial proliferation and tube formation [58]. Another group reported that VEGF bound to RPTPβ/ζ and that Ptn interrupted this binding to inhibit VEGF-induced endothelial migration [59, 60]. Additionally, Ptn suppressed the expression of VEGF receptor 2 (VEGFR2), thereby inhibiting VEGF-induced endothelial proliferation and migration [61].…”
Section: Discussionmentioning
confidence: 99%